Pengaruh Penggunaan Modal Kerja Terhadap Peningkatan Profitabilitas - Rifani Akbar Sulbahri (Akuntansi dan Manajemen, 2022)
Decision-making process in source of funds management is crucial for companies. This is due to its effect on company’s financial structure affecting profitability. This is the main reason why working capital is discussed in increasing company profits because working capital is a short-term expenditure of the company in operational activities that in line with the company's continuous activities as well as being the main supporter of the company's performance. GAP research shows that working capital affects the ability to obtain profitability. This is contrary to the theory where high working capital should mean high profitability. Refering to the findings on the effect of working capital (WCT) and Profitability (ROE) variables, the following conclusions can be drawn: Working capital (WCT) has a significant positive effect on profitability (ROE), this is because t is calculated for the variable WCT is 2.215 with a significance of 0.001 the t-count value which is 2.215 is greater than the t-table value, which is 2.004 (t-count > t-table). And it can also be indicated from the company's activities in funding the cash invested, which is very influential with the company's operational activities. If the working capital turnover is high, it shows the more productive the working capital used, so that it can get profits faster.